1997
DOI: 10.1159/000129543
|View full text |Cite
|
Sign up to set email alerts
|

Prolongation of Discordant Heart Xenograft Survival after Liver Hemoperfusion: Role of Nonparenchymal Liver Cells

Abstract: In the discordant guinea pig (GP)-to-rat combination, heart xenografts are hyperacutely rejected. The aim of the present study was to demonstrate that a donor-species-specific extracorporeal liver hemoperfusion can prolong survival of discordant heart xenografts and to specify the role of nonparenchymal cells. GP hearts were grafted into Brown Norway rats (group 1). In group 2, heart xenografting was carried out immediately after a 15-min GP hemoperfusion. In group 3, Kupffer cells of the GP liver were blockag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…It has been reported that blocking KCs by GdCl 3 can reduce ischemia/reperfusion injury24–26 and have protective effects on grafts in LT 27–29. Nevertheless, other studies have revealed that KCs play a protective role in liver ischemia/reperfusion injury and transplantation,30–35 and the animal survival rate is significantly decreased because of KC blockade;32, 33 this is consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that blocking KCs by GdCl 3 can reduce ischemia/reperfusion injury24–26 and have protective effects on grafts in LT 27–29. Nevertheless, other studies have revealed that KCs play a protective role in liver ischemia/reperfusion injury and transplantation,30–35 and the animal survival rate is significantly decreased because of KC blockade;32, 33 this is consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…For example, intravenous MDP was used to activate guinea pig liver macrophages to absorb cytotoxic antibodies and protect heart xenografts [114].…”
Section: Macrophage Activation In Animal Modelsmentioning
confidence: 99%